Is the time between onset of pain and restoration of patency of infarct-related artery shortened in patients with myocardial infarction? The effects of the Kielce Region System for Optimal Management of Acute Myocardial Infarction - Marcin Sadowski; Agnieszka Janion-Sadowska; Jacek Kurzawski; Janusz Sielski; Łukasz Zandecki; Marianna Janion; Lech Poloński (Studia Medyczne, 2014)
Introduction : The importance of delay in the restoration of infarct-related artery patency in patients with myocardial infarction was discussed, and actions were undertaken in the Kielce Region aimed at shortening this time within the System for Optimal Management of Acute Myocardial Infarction. Aim of the research: To evaluate the effectiveness of shortening time delays during transport of patients and diagnostics of myocardial infarction in the Kielce Region. Material and methods: Time delays were analysed in 5,934 patients with ST-segment elevation myocardial infarction (STEMI), hospitalised in cardiology wards with interventional cardiology on 24-hour duty, during the period 2008–2012. Time delays were analysed between the onset of myocardial infarction pain and undertaking treatment – T1 and T2 time – within which a patient with myocardial infarction, after admission to hospital, has intervention performed on infarct-related coronary artery. Results : During the period 2008–2012, the median T1 time was successfully shortened from 355 to 203 min, and the T2 time from 101 to 48 min. Conclusions: The effectiveness of the system was confirmed, and the necessity for further improvement of the system indicated.